Pengaruh Slow Stroke Back Massage Terhadap Kualitas Tidur Ibu Post Sectio Caesarea di RS. Bhayangkara Bengkulu - Anninah Anninah; Asmawati Asmawati; Sariman Pardosi (Poltekkes Kemenkes Bengkulu, 2020)
Mother with sectio caesarea needs sleep for recovery and treatment. Mother with sleep disorders have a negative impact on quality of maternal health. Purpose of this research to determined effect of slow stroke back massage on quality of post-sectio caesarea mother's sleep. This study used quasi experimental with pre-test and post-test with control group design. Samples were taken mother with sectio caesarea at RS. Bhayangkara Bengkulu with 2 groups of consecutive sampling technique and each group obtain 15 respondents. The analysis used independent sample t-test at α <5%. The result of intervention group and control group before being given a slow stroke back massage were each average of sleep quality scores 10.27 and 8.00, meanwhile the result of intervention group and control group after being given a slow stroke back massage were each average of sleep quality scores 8.80 and 7.60. The slow stroke back massage teraphy need to restore the quality of post-sectio caesarea mother's sleep in RS. Bhayangkara Bengkulu.